THE EFFECT OF DEMOCRATIC HAOS REGARDING THE SOCIOPROFESSIONAL CATEGORIES - Mirela Cristiana NILĂ STRATONE (Challenges of the Knowledge Society, 2018)
The democratic social framework has the role of ensuring stability, social protection, equal opportunities, and above all ensuring the rights and freedoms of citizens. The right to freedom of expression leaves a less prepared, unprotected population of information on the selection of information. This category of population is representative in the population of a country and is exposed to unqualified opinion. The issue raised in this article is based on the fact that, following the formation of an unqualified opinion, the individual goes to action. This action will give rise to anti-social effects that the author will consider viable. Hence, manipulation and social chaos are born, leading directly to antagonisms between socio-professional categories. That is why we can talk about the wrong attitudes towards the workers in any field of activity. There is a general strife of all against all. No one is considered competent, a negative label is placed on each profession, because professionals in any field are discredited, accused without necessarily being guilty. All these are directed and serve interests of social destabilization. The general chaos installed in Romanian society is also an effect of the non-elites' action at the level of the government's leadership. Above all, a strong footprint puts it the promotion of new values, non-values, affecting the future of the young